Workplace Ostracism: A Systematic Literature Review - Andreas Nova IGW; Sundring Pantja Djati; Hendy Tannady; Sukmo Hadi Nugroho (Dinasti International Journal of Education Management and Social Science, 2025)
The purpose of this study is to review research on workplace ostracism and its impact on employees and analyze gaps that require further research. The methodology used was collecting articles on workplace ostracism published in Scopus between 2020 and 2025 using open access. These articles cover various industries such as healthcare, manufacturing, consumer goods, hospitality, and education, with over 50% of the research conducted in Asian countries, primarily China and Pakistan. The study found that workplace ostracism occurs at various organizational levels and is associated with factors such as performance and job stress. Other factors such as leadership and culture also influence employee behavior. Key findings indicate that workplace ostracism negatively impacts employee psychological aspects, such as burnout, job satisfaction, self-esteem, and well-being. Employees who feel neglected feel unappreciated, which can decrease performance and lead to information avoidance, as well as increase intentions to leave the job. Ostracism also impacts employees' personal relationships, including with family. Therefore, it is important for organizations to identify and prevent ostracism to maintain employee psychological health and organizational performance.